Mud cracks promote colonization by pioneer saltmarsh plants - Jiang, Can; Li, Xiuzhen; Zhao, Wenzhen; Xue, Liming; Su, Lin (Frontiers in Marine Science, 2023)
Saltmarshes are valued as key buffering ecosystems against global climate change and sea level rise. However, the knowledge deficit regarding links between colonization of saltmarsh fringes by plants and mud cracking in the lateral dimension considerably limits our understanding of marsh resilience. Here, the role of mud cracks in colonization by saltmarsh plants was investigated. A combination of field experiments, remote sensing, and experimental results revealed that: (1) potential mud cracking zones were formed at the seaward edge of saltmarshes under the influence of tide-induced wetting–drying cycles, where mud cracks were extensively distributed and colonized by new seedlings. (2) The seedling density in the mud cracks was higher than that in the patches, and seedlings in the mud cracks sprouted earlier than those in the patches. The results implied that mud cracking enhanced colonization by saltmarsh plants, rather than being a water stressor. (3) The two main ecological functions of mud cracks in saltmarsh colonization were acting as “seed traps” and “seedling growth promoters.” (4) Mud cracking could be a key factor influencing saltmarsh resilience, especially by promoting the colonization and dispersal of saltmarsh plants. Rapid colonization of potential zones with mud cracks could occur as soon as seeds are available. Our results could facilitate the development of appropriate saltmarsh rehabilitation strategies.